Green synthesis method of novel chitosan-COFs aerogel and application of novel chitosan-COFs aerogel in oil-water separation
The preparation of chitosan-COFs aerogel by mechanochemical method solves the problem of harsh conditions for the synthesis of COFs aerogels, and achieves efficient and environmentally friendly oil-water separation effect. It has light weight, high porosity and superhydrophobicity, and is suitable for oil-water separation in complex environments.
Patent Information
- Application Number
- CN202510788402.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-13
- Publication Date
- 2025-07-29
AI Technical Summary
The existing COFs aerogel synthesis method is harsh, which limits its large-scale rapid preparation in industrial environments, and the powder is not easy to form, resulting in low adsorption capacity and speed, and is prone to secondary contamination.
Mechanochemical method is used to prepare chitosan-COFs aerogels, and the reaction is promoted by mechanical force, combined with the cross-linking, silanization and eutectic methods of chitosan and COFs to form a high porosity, superhydrophobic CBAB-TAPT-BPA aerogel.
It achieves efficient oil-water separation, light weight, high porosity and superhydrophobicity, significantly improves the adsorption performance of oily substances, and has excellent recyclability and environmental protection.
Smart Images

Figure CN120381825A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the application of aerogels in oil-water separation, and relates to the green synthesis of aerogels and the treatment of oil pollutants in water. Specifically, it relates to a green synthesis method without inert gas protection, simple operation and environmental friendliness, and prepares a superhydrophobic CBAB-TAPT-BPA aerogel by mechanically grinding COFs powder and chitosan CS. Background Art
[0002] Oil pollution caused by various human activities (oil spills caused by oil production, transportation, shipping and storage) and natural events (natural seepage) has had a serious impact on the environment, ecosystem and economy. Researchers have proposed different methods to deal with oil spills, such as oil containment boom systems, in-situ burning, bioremediation and adsorption material recovery. Porous adsorption materials, such as foams, aerogels and sponges with superhydrophobicity and compressibility, have been widely used in oil spill treatment due to their high adsorption efficiency, selective adsorption, reusability and low pollution. The driving force for the oil adsorption capacity of adsorption materials comes from van der Waals forces and capillary rise effects. Therefore, the research on oil spill recovery adsorption materials mainly focuses on hydrophobic surface modification, pore size control and enhanced compressibility.
[0003] For most porous adsorption materials, randomly distributed pores generate great resistance to the inflow of oil into the internal space of the adsorption material, resulting in low adsorption capacity and adsorption rate. Porous materials with aligned channels are better candidates for reducing the tortuosity of porous adsorption materials and making full use of capillary forces. COFs are known as a new type of porous organic crystalline polymer and have broad application prospects in the field of oil-water separation due to their regular pore size, large specific surface area, good thermal / chemical stability and easy modification. However, most of the COFs developed so far are mainly powder crystals synthesized by solvothermal methods. The poor insolubility and processability of COFs powder make it difficult to form, limiting its practical application. To solve this problem, people have tried to obtain COFs monolithic materials through various strategies. COFs monolithic materials not only retain the inherent advantages of the original COFs and prevent COF particle aggregation, but also inherit the advantages of monolithic materials being easy to handle and convenient for recycling.
[0004] Chitosan (CS) is a natural product extracted from chitin, which has many advantages, including low cost, biocompatibility, non-toxicity, and biodegradability. CS contains abundant amino and hydroxyl groups, which are beneficial for forming hydrogen bonds or electrostatic interactions with other components. At the same time, strong covalent bonds can also be established to form a highly connected network and improve mechanical stability. In recent years, COFs / CS aerogels have received increasing attention due to their light weight, low density, and high porosity, showing great potential in environmental remediation. On the one hand, shaping the hydrophobic COFs powder and CS into a three-dimensional network structure to form CS / COFs aerogel not only improves the material plasticity and mechanical properties of COFs but also endows the aerogel material with a hierarchical porous structure, enhancing the transport of pollutants and thus having excellent oil-water separation selectivity. On the other hand, after being modified by silanization reagents and the hydrophobic characteristics of COFs itself, the aerogel material can be given superhydrophobic characteristics and excellent oil absorption capacity, making it have broad application prospects in the field of oil-water separation.
[0005] At present, the preparation of most aerogels containing COFs requires relatively harsh reaction conditions, such as long-term high-temperature reflux, protection of inert gas, or high pressure, which limits their large-scale and rapid preparation in industrial environments. Therefore, it is very necessary to use green synthesis methods that can improve efficiency and reduce pollution. The mechanochemical method usually does not require complex solvents and long reaction steps. It directly promotes the reaction through mechanical force and can obtain the target product in a short time. During the synthesis process, organic solvents can be reduced or not used at all, which conforms to the principles of green chemistry. At the same time, it can also increase the contact area between reactants, improve the reaction rate, and thus promote the overall efficiency of the reaction. Due to the reduced demand for precious catalysts and complex treatment processes, the mechanochemical method is relatively economical, reducing the synthesis cost of COFs and having better practical application potential.
[0006] This invention uses the mechanochemical method to prepare a CBAB-TAPT-BPA aerogel for efficient oil-water separation. This aerogel significantly improves the adsorption performance for oil substances, solving the problems of difficult recovery and easy secondary pollution of COFs. Due to the hierarchical porous structure and high porosity of the aerogel, it has excellent adsorption capacity for carbon tetrachloride in water, reaching 8639 mg / g. In addition, the aerogel exhibits excellent recyclability, and the adsorption capacity still remains 93% after five cycles. It has extremely high oil-water separation efficiency for light oil (n-hexane) on water and heavy oil (chloroform) under water, reaching 99.89% and 99.52% respectively. This green synthesis, simple process, low-cost, high-porosity, and hydrophobic aerogel material developed by this invention has important industrial value. Summary of the Invention
[0007] Developing aerogel materials with high porosity and hydrophobicity has important research value. Especially for aerogel materials used in high-strength oil-water separation in complex environments, they are currently relatively scarce. In view of this problem, the present invention discloses a CBAB-TAPT-BPA aerogel for efficient oil-water separation and its preparation method.
[0008] The object of the present invention is achieved by the following technical solutions:
[0009] A preparation method of a CBAB-TAPT-BPA aerogel for efficient oil-water separation, comprising the following steps:
[0010] (1) First, dissolve chitosan (CS) in an acidic aqueous solution to obtain a viscous, clear and transparent liquid, and then add 4,4-biphenyldialdehyde (BPA) dissolved in DMSO for cross-linking reaction. After the reaction is complete, chitosan-biphenyldialdehyde hydrogel (CB) is obtained;
[0011] (2) After the reaction in step (1) is completed, add an anhydrous ethanol / distilled water mixture and 3-aminopropyltriethoxysilane (APTES) for hydrophobization and amination reactions. After removing impurities, dry to obtain a CS-BPA-APTES (CBA) solid;
[0012] (3) Add BPA to step (2), with glacial acetic acid as a catalyst and abrasive, to obtain a CBAB substrate. After the reaction is completed, dry and reserve it;
[0013] (4) Place 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (TAPT) and p-toluenesulfonic acid (PTSA) in a mortar, with water as an abrasive, and grind to form a eutectic (TAPT-PTSA);
[0014] (5) Mix the samples prepared in step (3) and step (4) in a mortar, add BPA, and at the same time use 1,4-dioxane as an abrasive and catalyst for grinding. After grinding is completed, wash the sample with a solvent, and place the sample after removing impurities in a mold for freeze-drying to finally obtain a CBAB-TAPT-BPA aerogel with light weight, high porosity and superhydrophobicity.
[0015] Preferably, the acidic aqueous solution selected in step (1) is one of hydrochloric acid or acetic acid; more preferably acetic acid; the concentration of the acidic aqueous solution is 1-3%; more preferably 3%.
[0016] Preferably, the temperature for dissolving chitosan (CS) in the acidic aqueous solution in step (1) is 50-60°C; more preferably 60°C; the reaction time is 4-5 hours; more preferably 5 hours; the reaction temperature for adding the cross-linking agent is 50-60°C; more preferably 60°C; the reaction time is 4-5 hours; more preferably 5 hours.
[0017] Preferably, the concentration of 3-aminopropyltriethoxysilane described in step (2) is 8-10%, more preferably 10%.
[0018] Preferably, the temperature for the amination reaction in step (2) is 50-60 °C; more preferably 60 °C; the reaction time is 10-12 hours; more preferably 12 hours; the drying temperature is 80-100 °C; more preferably 90 °C; the drying time is 50-60 minutes; more preferably 60 minutes.
[0019] Preferably, the solvent used to remove impurities in step (2) is absolute ethanol.
[0020] Preferably, the grinding temperature in step (3) is room temperature; the grinding time is 15-20 minutes; more preferably 20 minutes; the drying temperature after the reaction is complete is 80-100 °C; more preferably 90 °C; the drying time is 50-60 minutes; more preferably 60 minutes.
[0021] Preferably, the reaction temperature for grinding the eutectic product (TAPT-PTSA) in step (4) is room temperature; the grinding time is 10-15 minutes; more preferably 15 minutes.
[0022] Preferably, the grinding temperature in step (5) is room temperature; the grinding time is 50-60 minutes; more preferably 60 minutes; the freeze-drying temperature is -60 °C, and the freeze-drying time is 24-48 hours; more preferably 48 hours.
[0023] Preferably, the solvents used to remove impurities in step (5) are methanol, tetrahydrofuran, N,N-dimethylformamide, and dichloromethane.
[0024] Application of a novel chitosan-COFs aerogel CBAB-TAPT-BPA in oil-water separation.
[0025] Preferably, in the above application, the oils include six kinds of light oils and heavy oils in total.
[0026] More preferably, the light oils are n-hexane, N,N-dimethylformamide, and ethyl acetate; the heavy oils are dichloromethane, chloroform, and carbon tetrachloride.
[0027] The present invention prepares a CBAB-TAPT-BPA aerogel material with efficient oil-water separation, which has characteristics such as light weight, high porosity and superhydrophobicity. The key to the oil-water separation performance lies in the internal structure and surface characteristics. The porous structure provides a long penetration channel for oil or water in the oily wastewater, and the high porosity can improve the separation flux of the separation material for the oily wastewater. The prepared aerogel material is used as a filter layer. When a mixture of oil (n-hexane, chloroform) and water is poured into the designed oil-water separation device, the oil with a density greater than that of water can pass through the aerogel channel and be filtered out from the lower end of the device, while the water is blocked outside the aerogel and cannot penetrate into the interior of the aerogel, thus achieving the oil-water separation effect. The water contact angle of the prepared CBAB-TAPT-BPA aerogel can reach 151.0°. It has extremely high oil-water separation efficiency for light oil (n-hexane) on water and heavy oil (chloroform) under water, reaching 99.89% and 99.52% respectively, and the oil adsorption capacity for carbon tetrachloride reaches 8639 mg / g.
[0028] In summary, the present invention prepares an aerogel using functionalized chitosan as a substrate, which has a wide source and low price. Through the green synthesis method of mechanical grinding, the prepared CBAB-TAPT-BPA aerogel has the advantages of light weight, high porosity, superhydrophobicity and efficient oil-water separation, and has good adsorption performance and adsorption rate for light oil on water and heavy oil under water. Through a simple mechanochemical method, the rapid preparation of a hydrophobic aerogel is realized, and at the same time, the application potential of the aerogel material in the field of oil-water separation is expanded.
[0029] Other features and advantages of the present invention will be described in detail in the subsequent specific implementation part.
[0030] The beneficial effects of the present invention are as follows:
[0031] 1. The present invention provides a preparation method for CBAB-TAPT-BPA aerogel with rapid synthesis, environmental friendliness and simple operation.
[0032] 2. The mechanical force method of the present invention is carried out under conventional conditions, without high temperature, high pressure or inert gas protection, which simplifies the experimental steps.
[0033] 3. The reaction of the present invention only uses a small amount of liquid to assist grinding, eliminating the use of a large amount of organic solvents, reducing the reaction cost and at the same time reducing the harm to the environment.
[0034] 4. The prepared CBAB-TAPT-BPA aerogel of the present invention has the advantages of light weight, high porosity, superhydrophobicity and efficient oil-water separation. Brief Description of the Drawings
[0035] Figure 1It is the preparation flow chart of CBAB-TAPT-BPA aerogel prepared in Example 1.
[0036] Figure 2 It is the water contact angle diagram of CBAB-TAPT-BPA aerogel prepared in Example 1, where (a) is the contact angle of CBA, (b) is the contact angle of TAPT-BPA-COF, and (c) is the contact angle of CBAB-TAPT-BPA aerogel.
[0037] Figure 3 It is the infrared spectrum diagram of CBAB-TAPT-BPA aerogel prepared in Example 1.
[0038] Figure 4 It is the XRD diagram of CBAB-TAPT-BPA aerogel prepared in Example 1.
[0039] Figure 5 It is the oil adsorption capacity diagram of CBAB-TAPT-BPA aerogel prepared in Example 1.
[0040] Figure 6 It is the oil adsorption process diagram of CBAB-TAPT-BPA aerogel prepared in Example 1.
[0041] Figure 7 It is the oil-water separation cycle efficiency diagram of CBAB-TAPT-BPA aerogel prepared in Example 1, where (a) is the oil-water separation efficiency of the aerogel for n-hexane on the water supernatant oil, and (b) is the oil-water separation efficiency of the aerogel for chloroform on the heavy oil under the water. Detailed implementation mode
[0042] For a better understanding of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0043] The present invention proposes a hydrophobic, high-adsorption-capacity and highly efficient oil-water separation CBAB-TAPT-BPA aerogel and its preparation method. The present invention crosslinks CS and BPA to lay a foundation for improving the stability of CBAB-TAPT-BPA aerogel, and then adds APTES to carry out a silanization reaction with the -OH on CS to achieve the first-step hydrophobic modification; after the silanization reaction, with exposed -NH2, after reacting with BPA by a mechanical method, aldehyde groups can be provided for the in-situ growth of TAPT-BPA-COFs; finally, a eutectic (TAPT-PTSA) is used to promote the in-situ growth of COFs and the method of freeze-drying to prepare CBAB-TAPT-BPA aerogel.
[0044] The present invention will be further explained and illustrated below in conjunction with the accompanying drawings of the specification and specific embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of them. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in the present application without creative efforts belong to the scope of protection of the present application.
[0045] Example 1
[0046] This example provides a hydrophobic and highly efficient oil-water separation CBAB-TAPT-BPA aerogel and its preparation method, including the following steps:
[0047] S1. Dissolve 322 mg of chitosan in 20 mL of 3% aqueous acetic acid solution, react on an electric heating plate at 60 °C for 5 hours, then add 210 mg of 4,4-biphenyl dialdehyde, dissolve it with 8 mL of DMSO, and continue to react at 60 °C for 5 hours; after the reaction, add a 1:1 mixture of 100 mL of absolute ethanol / distilled water and 10 mL of APTES, and react at 60 °C for 12 hours; after the reaction, filter by suction, wash with absolute ethanol multiple times, and then dry in an oven at 90 °C for 60 minutes. After taking out, obtain the CS-BPA-APTES solid for standby.
[0048] S2. Place the solid obtained in S1 and 210 mg of 4,4-biphenyl dialdehyde in a mortar, add 60 μL of glacial acetic acid as a grinding agent and catalyst, grind at room temperature under mechanical force for 20 minutes, and dry in an oven at 90 °C for 60 minutes to obtain the CBAB substrate. After taking out, set it aside for standby.
[0049] S3. Mix 126 mg of TAPT and 101 mg of PTSA in a mortar, grind at room temperature under mechanical force for 15 minutes until the sample is dry, and obtain the eutectic product TAPT-PTSA.
[0050] S4. Mix the eutectic products of S2 and S3 in a mortar, add 112.14 mg of 4,4-biphenyl dialdehyde and 60 μL of 1,4-dioxane as a grinding agent and catalyst, grind at room temperature under mechanical force for 60 minutes; after the reaction is complete, wash with solvents such as methanol, tetrahydrofuran, N,N-dimethylformamide, and dichloromethane to remove impurities such as PTSA and polymers. After removing the impurities, place it in a rubber mold with a size of 1×1×1 cm and freeze-dry at -60 °C for 24 hours to finally synthesize the aerogel with light weight, high porosity and superhydrophobicity in this example.
[0051] Figure 2It is the water contact angle diagram of the CBAB-TAPT-BPA aerogel prepared in Example 1. After the silanization reaction and in-situ growth of TAPT-BPA-COFs, the hydrophobicity of the CBAB-TAPT-BPA aerogel is significantly increased, and the water contact angle is 151.0°. Therefore, the result of the water contact angle proves that the CBAB-TAPT-BPA aerogel has good hydrophobic properties.
[0052] Figure 3 It is the infrared spectrum diagram of the CBAB-TAPT-BPA aerogel prepared in Example 1. The stretching vibration peaks of the -C=N bond appear in both COFs and the CBAB-TAPT-BPA aerogel at 1506 cm -1 The stretching vibration peak of the -Si-O-Si bond appears in the CBAB-TAPT-BPA aerogel at 1012 - 1033 cm -1 Therefore, the result of the infrared spectrum proves the successful modification of the silanization reaction and the successful in-situ growth of COFs.
[0053] Figure 4 It is the X-ray diffraction pattern of the CBAB-TAPT-BPA aerogel prepared in Example 1. The crystallization characteristics of the CS aerogel show two broad peaks at 2θ = 12.05° and 20.03°, which are due to the hydrogen bonds formed by the interaction between the amino group and the hydroxyl group of CS. A typical peak of the synthesized COFs is observed in the CBAB-TAPT-BPA aerogel at 2θ = 2.36°, and this peak is consistent with the COFs peak simulated in Materials Studio. The clearly recognizable COFs peak present in the CBAB-TAPT-BPA aerogel spectrum indicates the presence of a complete crystal structure within the CBAB-TAPT-BPA aerogel. Therefore, the XRD result establishes the successful preparation of the CBAB-TAPT-BPA aerogel.
[0054] In summary, the present invention provides a green micro-liquid assisted grinding technology for synthesizing a superhydrophobic and highly efficient oil-water separation CBAB-TAPT-BPA aerogel and its preparation method. It includes crosslinking chitosan and 4,4-biphenyl dialdehyde, and after crosslinking, carrying out silanization and amination reactions with APTES, and then reacting with 4,4-biphenyl dialdehyde to provide sites for the in-situ growth of COFs. Also, the method of using the eutectic of TAPT and PTSA promotes the in-situ growth of COFs, and finally a superhydrophobic and highly efficient oil-water separation CBAB-TAPT-BPA aerogel is prepared. The crosslinking with 4,4-biphenyl dialdehyde enhances the stability of the aerogel, and after modification with the APTES silanization reagent and the hydrophobic characteristics of COFs itself, the aerogel is endowed with superhydrophobic characteristics and excellent oil absorption capacity, making it have broad application prospects in the field of oil-water separation.
[0055] Example 2
[0056] The absorption capacity of CBAB-TAPT-BPA aerogel was tested for different organic solvents (n-hexane, N,N-dimethylformamide, ethyl acetate, dichloromethane, chloroform, carbon tetrachloride). The CBAB-TAPT-BPA aerogel was immersed in different kinds of oils for 1 minute, and the absorption capacity of the CBAB-TAPT-BPA aerogel was calculated. Meanwhile, to evaluate the recyclability of the CBAB-TAPT-BPA aerogel, after the adsorption reached saturation, the CBAB-TAPT-BPA aerogel was washed with absolute ethanol and dried under vacuum to facilitate the desorption process. Subsequently, five cycles could be repeated to achieve the recycling goal.
[0057] As Figure 5 shown, the adsorption capacity of n-hexane was 3600 mg / g, that of ethyl acetate was 3857 mg / g, that of N,N-dimethylformamide was 4500 mg / g, that of dichloromethane was 5574 mg / g, that of chloroform was 8388 mg / g, and that of carbon tetrachloride was 8639 mg / g. In addition, the aerogel also exhibited excellent recyclability, and the adsorption capacity remained above 93% after five cycles.
[0058] Figure 6 It depicts that when n-hexane was dropped onto the surface of CBAB-TAPT-BPA aerogel, it was absorbed by the aerogel in an instant, indicating that the aerogel also has good adsorption performance for organic solvents. This rapid adsorption behavior further confirmed the lipophilicity of the aerogel, making it suitable for oil-water separation applications. In contrast, when water droplets contacted the surface of CBAB-TAPT-BPA aerogel, they were not absorbed but remained on the surface of the aerogel, forming water beads. This indicates that the aerogel is hydrophobic and has a weak adsorption capacity for water. This hydrophobicity is a very desirable property in oil-water separation applications because it can prevent the aerogel from absorbing water, thereby improving its selectivity and efficiency in the oil-water separation process.
[0059] Figure 7Describes the continuous gravity-driven process of CBAB-TAPT-BPA aerogel. Chloroform and n-hexane were stained with Oil Red O, and water was stained with methylene blue. For the oil / water separation efficiency of chloroform / water, first, water (blue) was poured into the funnel, and no water seeped out from the aerogel. Then, chloroform (red) was poured in. After chloroform came into contact with the CBAB-TAPT-BPA aerogel, it was quickly absorbed and formed an oil film, which could significantly reduce the contact area between water and the aerogel, thus promoting oil / water separation. As it approached its absorption limit, chloroform (red) was gradually poured into the beaker, while water (blue) remained in the funnel. After 5 minutes of complete separation, no water seeped out from the aerogel. For the oil / water separation efficiency of n-hexane / water, first, n-hexane (red) was poured into the funnel. After n-hexane came into contact with the CBAB-TAPT-BPA aerogel, it was quickly absorbed. Then, water (blue) was poured in. n-hexane (red) was completely poured into the beaker, while water (blue) remained in the funnel. After 5 minutes of separation, no water seeped out from the aerogel. The CBAB-TAPT-BPA aerogel showed good oil / water separation ability. As shown in Figure 7 (a) and (b), the oil / water separation efficiency of chloroform / water was 99.62%, and the oil / water separation efficiency of n-hexane / water was 99.76%. After ten times of oil / water mixture separation, the aerogel still maintained its porous structure and morphology, indicating its good stability and durability, and could be used for long-term continuous oil / water separation without changing its original properties or structure.
[0060] In summary, the present invention provides a green preparation method for synthesizing CBAB-TAPT-BPA aerogel with strong hydrophobicity and high oil / water separation efficiency by a micro-liquid-assisted grinding technique. It includes cross-linking chitosan and BPA, followed by silanization and amination reactions with APTES, and then reacting with BPA to provide sites for the in-situ growth of TAPT-BPA-COFs. The method of using the eutectic of TAPT and PTSA is adopted to in-situ grow TAPT-BPA-COFs, and finally, a hydrophobic and highly efficient oil / water separation CBAB-TAPT-BPA aerogel is prepared. The cross-linking of the aerogel enhances its stability. After being modified with the APTES silanization reagent and the hydrophobic characteristics of TAPT-BPA-COFs itself, the aerogel can be endowed with strong hydrophobic characteristics and excellent oil absorption ability, realizing efficient oil / water separation, and making it have broad application prospects in the field of oil / water separation.
Claims
1. A novel chitosan-COFs aerogel CBAB-TAPT-BPA, characterized in that, The preparation method comprises the following steps: 1) First, dissolve chitosan CS in an acidic aqueous solution to obtain a viscous, clear and transparent liquid, and then add 4,4-biphenyldialdehyde BPA dissolved in DMSO for cross-linking reaction. After the reaction is complete, chitosan-biphenyldialdehyde hydrogel CB is obtained; 2) After the reaction in step 1) is completed, add a mixture of anhydrous ethanol / distilled water and 3-aminopropyltriethoxysilane APTES for hydrophobization and amination reactions. After removing impurities, dry to obtain CS-BPA-APTES solid; 3) Add BPA to step 2), use glacial acetic acid as a catalyst and abrasive, and grind to obtain CBAB substrate. After the reaction is completed, dry and reserve; 4) Place 2,4,6-tris(4-aminophenyl)-1,3,5-triazine TAPT and p-toluenesulfonic acid PTSA in a mortar, use water as an abrasive, and grind to form eutectic TAPT-PTSA; 5) Mix the samples prepared in step 3) and step 4) in a mortar, add BPA, and at the same time use 1,4-dioxane as an abrasive for grinding. After grinding is completed, wash with a solvent, and place the sample after removing impurities in a mold for freeze-drying to finally obtain a CBAB-TAPT-BPA aerogel with light weight, high porosity and superhydrophobicity.
2. A novel chitosan-COF aerogel CBAB-TAPT-BPA according to claim 1, characterized in that, The acidic aqueous solution in step 1) is hydrochloric acid or acetic acid, and the concentration of the acidic aqueous solution is 1-3%.
3. A novel chitosan-COF aerogel CBAB-TAPT-BPA according to claim 1, characterized in that, The concentration of 3-aminopropyltriethoxysilane in step 2) is 8-10%.
4. A novel chitosan-COFs aerogel CBAB-TAPT-BPA according to claim 1, characterized in that, In step 1), the temperature for dissolving chitosan (CS) in acetic acid aqueous solution is 50-60 °C, and the reaction time is 4-5 hours; the reaction temperature for adding the cross-linking agent is 50-60 °C, and the reaction time is 4-5 hours.
5. A novel chitosan-COF aerogel CBAB-TAPT-BPA according to claim 1, characterized in that, In step 2), the temperature for amination reaction is 50-60 °C, and the reaction time is 10-12 hours; the drying temperature is 80-100 °C, and the drying time is 50-60 minutes.
6. A novel chitosan-COFs aerogel CBAB-TAPT-BPA according to claim 1, characterized in that In step 3), the grinding temperature is room temperature, and the grinding time is 15-20 minutes; the drying temperature is 80-100 °C, and the drying time is 50-60 minutes; In step 4), the grinding temperature for forming eutectic by grinding is room temperature, and the grinding time is 10-15 minutes; In step 5), the grinding temperature for synthesizing the aerogel is room temperature, and the grinding time is 50-60 minutes; the freeze-drying temperature is -60 °C, and the freeze-drying time is 24-48 hours.
7. A novel chitosan-COF aerogel CBAB-TAPT-BPA aerogel according to claim 1, characterized in that, The solvent used to remove impurities in step 2) is anhydrous ethanol; the solvents used to remove impurities in step 5) are methanol, tetrahydrofuran, N,N-dimethylformamide, and dichloromethane.
8. Application of a novel chitosan-COFs aerogel CBAB-TAPT-BPA according to any one of claims 1-7 in oil-water separation.
9. The application according to claim 8, characterized in that, The oil is light oil or heavy oil, specifically one or more of n-hexane, N,N-dimethylformamide, ethyl acetate, dichloromethane, chloroform, and carbon tetrachloride.